2017
DOI: 10.1001/jamaophthalmol.2017.2583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Trial and Systematic Review Outcomes for the 4 Most Prevalent Eye Diseases

Abstract: IMPORTANCE Suboptimal overlap in outcomes reported in clinical trials and systematic reviews compromises efforts to compare and summarize results across these studies.OBJECTIVES To examine the most frequent outcomes used in trials and reviews of the 4 most prevalent eye diseases (age-related macular degeneration [AMD], cataract, diabetic retinopathy [DR], and glaucoma) and the overlap between outcomes in the reviews and the trials included in the reviews. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…This suggests that, approximately 7 in 10 studies that reviewers include are not incorporated into the meta-analysis for the main outcome, and 1 in 4 studies are not incorporated into the meta-analysis for any outcome. In previous work, we demonstrated poor overlap between outcomes in clinical trials and reviews, and possible differences in the types of outcomes they examine [10,11]. For HIV/AIDS, we demonstrated that reviewers examined more long-term clinical outcomes and patient-centered outcomes than did clinical trialists.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This suggests that, approximately 7 in 10 studies that reviewers include are not incorporated into the meta-analysis for the main outcome, and 1 in 4 studies are not incorporated into the meta-analysis for any outcome. In previous work, we demonstrated poor overlap between outcomes in clinical trials and reviews, and possible differences in the types of outcomes they examine [10,11]. For HIV/AIDS, we demonstrated that reviewers examined more long-term clinical outcomes and patient-centered outcomes than did clinical trialists.…”
Section: Discussionmentioning
confidence: 74%
“…We [10,11] and others [20] have argued that, as stakeholders in a given field, systematic reviewers should both participate in the development of and adopt core outcome sets for that field. By broadening the participation in outcome prioritization efforts, this could potentially help ensure that the outcomes that are measured and reported in research are widely relevant and important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research has engaged clinical partners and addresses topics highly relevant to producing high quality reviews. Investigators at Cochrane Eyes and Vision US satellite have published methods papers on prioritizing reviews [13][14][15][16], practice guidelines [17][18][19], identifying clinical trials [20], strengths and limitations of data sources [21][22][23][24], and outcomes in Eyes and Vision trials and reviews [25][26][27][28][29], dissemination by co-publication [30], and network meta-analysis methods as applied to open angle glaucoma [31 32].…”
Section: Methods Researchmentioning
confidence: 99%